Changed Arctic-alpine food web interactions under rapid climate warming: implication for ptarmigan research - Henden, John-André; Ims, Rolf Anker; Fuglei, Eva; Pedersen, Åshild Ønvik (Wildlife Biology, 2017)
Source at https://doi.org/10.2981/wlb.00240 . Ptarmigan are herbivorous birds that are year-round residents of alpine and arctic ecosystems — presently subjected to the most rapid climate warming on earth. Yet, compared to other bird taxa there has been little climate impact research on ptarmigan. Ptarmigan population dynamics, in particular in the sub/low-arctic, appears to be strongly influenced by complex interactions with a suite of functionally diverse predators in the food webs. We review evidence supporting that the strength of such predator—ptarmigan interactions has been altered, most likely due to climate change, having led to rapidly declining ptarmigan populations and in some places national red listing. Predation-mediated population declines are likely linked to dampened population cycles of keystone mammal herbivores (inducing increased apparent competition/reduced apparent mutualism), altitudinal/latitudinal expansions of boreal mesopredators and possibly mismatched ptarmigan plumage colour in spring and fall. Yet, other rapid food web mediated impacts are likely to act bottom—up, such as phenological mismatches with food plants and competitive interactions with other irrupting herbivores. We advocate that ptarmigan researchers should team up with specialists on other taxa in order to adopt a food web approach to their research. Coordinated action of research teams, to make comparative studies among ptarmigan species or populations imbedded in food webs of varying structure or ambient climate, may be rewarding in the age of rapid ongoing climate changes.